Evaluations — a Key Towards Understanding the Affective Dimension of Translational Decisions - Tirkkonen-Condit, Sonja; Laukkanen, Johanna (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractAn analysis was done of the evaluative expressions which appeared in the think-aloud data derived from two sets of experiments on professional translators. The aim was to shed light on the affective side of translators' decisions by identifying their professional self-image and their subjective theories of translation. The theories were inferred from evaluations voiced at decision points between translation variants, whereas ideas about the self were inferred from statements concerning task performance and, in one instance, concerning the translator himself. It is presumed that the translators' decision-making throughout the process largely depends on these two factors.